Impact of Giant Cell Arteritis and Its Treatment on the Patient's Quality of Life: A Single-Center Self-Assessment Study - de Boysson, Hubert; Barakat, Clivia; Dumont, Anael; Boutemy, Jonathan; Martin Silva, Nicolas; Maigné, Gwénola; Nguyen, Alexandre; Lavergne, Amandine; Castan, Paul; Gallou, Sophie; Sultan, Audrey; Deshayes, Samuel; et al. (Frontiers in Medicine, 2021)
Little is known about the impact of giant cell arteritis (GCA) and its treatment on patient-reported physical, mental and psychic quality of life (QoL). In this monocentric study, a questionnaire was sent to the 100 last patients diagnosed with GCA and followed-up in a single tertiary center. Their physical, mental and psychic status were self-assessed via close-ended questions, the 12-item short form survey (SF-12) and the 15-item geriatric depression scale (GDS). We aimed to identify parameters that were significantly associated with moderate-to-severe disability in both physical and mental domains. Ninety patients were analyzable. Moderate to severe physical disability was found in 41 (46%) patients. In multivariate analysis, walking difficulties (OR, 95% CI 8.42 [2.98–26.82], p<0.0001), muscle mass and strength reduction (OR, 95% CI 4.38 [1.37–16.31], p=0.01) and age >80 (OR, 95% CI 4.21 [1.44–13.61], p=0.008) were independent findings associated with moderate to severe physical disability. Moderate to severe mental disability was found in 30 (33%) patients. In multivariate analysis, depressive mood (OR, 95% CI 11.05 [3.78–37.11], p<0.0001), felt adverse events attributable to glucocorticoids (OR, 95% CI 10.54 [1.65–213.1], p=0.01) and use of immunosuppressants (OR, 95% CI 3.50 [1.14–11.87], p=0.03) were independent findings associated with moderate to severe mental disability. There was a statistically significant negative correlation between GDS and the physical and/or mental disability scores (GDS and PCS-12: r = -0.33, p=0.0013; GDS and MCS-12: r=-0.36, p=0.0005). In conclusion, this study identified via a self-assessment of patients with GCA some medical and modifiable findings that significantly affect their physical and mental quality of life. A better knowledge of these factors may help improve the care of GCA patients.